Penggunaan Surat Edaran sebagai Tindak Lanjut atas Putusan Mahkamah Konstitusi - Irwansyah Irwansyah (Jurnal Penelitian Hukum De Jure, 2023)
The Constitutional Court’s decision is final and binding. It becomes effective as soon as it is pronounced in open. In practice, however, the Constitutional Court’s decision is followed by a variety of legal products, including laws, government regulations, and presidential regulations, and some even use circular letters. The method used in this paper is normative legal research. The purpose of this study is to analyze the circular letter as a follow-up to the Constitutional Court’s decision. The use of generalized letters in response to a Constitutional Court decision is deemed inappropriate. Because the dissemination is not a legal regulation, it is not necessary to follow the Constitutional Court’s decision when considering the law. In an ideal world, the Constitutional Court’s decision is followed by legislation.